Development of Qur'anic Study Thinking: Mapping the Qur'anic Studies Framework with the History of Ideas Framework - Hsb, Akmal Rizki Gunawan; Wathani, Syamsul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
In academic studies, the Qur'an has become a subject of intellectual discussions and has undergone significant development, engaging with the community on both interpersonal and inter-cognitive levels. Scholarly discourse on the Qur'an has progressed from descriptive-narrative analysis to critical analysis. This article examines the evolution of thought in Qur'anic studies within the academic community, using two analytical frameworks: the Framework of Qur'anic Studies and the history of ideas. The first framework categorizes the types and genres of Qur'anic studies, while the second analyzes shifts in thought related to studying the Qur'an. The article concludes that the evolution of thought in Qur'anic studies has resulted in a Traditionalist-Critical model, characterized by a transmission-theological dimension, with two distinct periods: the initial focus on idraki-ta'rifi (knowledge/understanding of the Qur'an) and a subsequent shift to tadris-naqdi studies (critical studies of the Qur'an). Additionally, the development of Qur'anic studies has led to the creation of a model within the Qur'anic Studies Framework, encompassing Al-Qira'ah Alquran (reading and reciting the Qur'an), Tafhim Alquran (linguistic study and interpretation), Ta'riful Qur'an (introducing new perspectives in Qur'anic knowledge), and Ta'limatul Qur'an (social-community context and analysis of Qur'anic teachings).